2021
DOI: 10.17718/tojde.961855
|View full text |Cite
|
Sign up to set email alerts
|

Development of Medical School Students’ Attitudes Towards Online Learning Scale and Its Relationship With E-Learning Styles

Abstract: This study aims at determining students' attitudes towards distance education/online learning through a scale developed by the authors and determine the relationship between these attitudes and e-learning styles. The study carried out on students of Canakkale Onsekiz Mart University Faculty of Medicine using the online system of the university., the sample group consists 815 students from different classes, the participation rate was 89.46%. Following the explanatory factor and confirmatory factor analysis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…No difference was found between the two groups when the students' attitudes towards online learning and online medical education were questioned; the low scores obtained showed that the students did not favour online education so much [45]. Considering online medical education based on the data we obtained, we found that, similar to online education, the students did not favour distance medical education and were against online education particularly in the area of practical applications.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…No difference was found between the two groups when the students' attitudes towards online learning and online medical education were questioned; the low scores obtained showed that the students did not favour online education so much [45]. Considering online medical education based on the data we obtained, we found that, similar to online education, the students did not favour distance medical education and were against online education particularly in the area of practical applications.…”
Section: Discussionmentioning
confidence: 64%
“…MSSATOLS: Developed by Yurdal et al [45], this scale is a measurement tool consisting of 22 items and two subscales. The scale is a five-point Likert type measurement tool.…”
Section: Participantsmentioning
confidence: 99%
“…Due to the pandemic's quick move to online education, many schools have an insufficient infrastructure. Infrastructure deficiency is more evident in fields that require laboratory work such as engineering (Andrzej, 2020) and medicine (Yurdal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Students' attitudes toward distance learning differ according to the studies. In some studies (Mathew and Chung, 2020;Avsheniuk et al, 2021), it is stated that especially the students' attitudes are positive, while in some studies (Bozavlı, 2021;Yurdal et al, 2021) it is clearly stated that their attitudes are negative. In addition, there are also studies (Akcil and Bastas, 2021) that indicate that students' attitudes are at a moderate level.…”
Section: Perception and Attitudes Toward Distance Learningmentioning
confidence: 99%
“…Students' attitudes toward online learning differ according to the studies. In studies conducted by Mathew and Chung (2020); Avsheniuk et al (2021) stated that students' attitudes are positive, while in different studies (Bozavli, 2021;Yurdal et al, 2021) it is clearly stated that students' attitudes are negative. There would be various reasons why students point out the negativity of online learning, whether learning environment conditions, access to a quality internet connection or adaptation to online learning during the MCO operation (Abrosimova, 2020;Balta-Salvador et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%